Catalytic and efficient synthesis of optically active terminal epoxides and 1,2-diols using a new lanthanum triflate assisted C1-symmetric bimetallic chiral salen cobalt complex - Patel, D.; Thakur, S. S.; Shinde, S. S.; Kumar, P. (Letters in Organic Chemistry, 2018)
The catalytic asymmetric synthesis of terminal epoxides and 1,2-diols via a hydrolytic kinetic resolution of racemic terminal epoxides using a new bimetallic chiral salen CoIII complex incorporated with La(OTf)3 as a catalyst is reported. The new bimetallic chiral salen CoIII complex bearing La(OTf)3 was prepared in a one-pot procedure by activation and bimetallic complex formation from the inactive Jacobsen chiral salen CoII complex (salen = N, N′-bis(3,5-di-tert-butylsalicylidene)-1,2- cyclohexane-diamine). We observed that C1-symmetric chiral bimetallic Co-complex coordinated with La(OTf)3 works as a chiral catalyst and remarkably increased the reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its monometallic analogues. La(OTf)3 plays a crucial role as an achiral Lewis acid in this process, which is supported by the experimental observation presented. To explore the absolute configuration of glycidyl butyrate a vibrational circular dichroism (VCD) spectra was calculated using density functional theory.